Meningkatkan Kemampuan Berpikir Kritis Siswa Menggunakan Model Problem Based Learning pada Materi Pengantar Ilmu Geografi di SMAN 12 Kendari - Nasiru, Ahmad Sadam; Kasmiati, Sitti; Hasanah, Nur (Jurnal Penelitian Pendidikan Geografi, 2026)
The critical thinking ability of students at SMAN 12 Kendari is still relatively low because the learning process tends to be teacher-centered. This study aims to: 1) determine student activities in applying critical thinking skills during learning the Introduction to Geography material, and 2) determine teacher activities after applying the Problem Based Learning (PBL) learning model on the same material. This study is a classroom action research. The results of the study indicate that: 1) the implementation of learning using PBL in cycle I obtained an average activity score of 2.7 by teachers and 2.5 by students, while in cycle II it increased to 3.5 for teachers and 3.6 for students; 2) students' critical thinking ability based on the Learning Objective Achievement Criteria of 75 also increased, where the percentage of completion in cycle I reached 70%, and increased in cycle II to 93.33%. Thus, it can be concluded that the application of the PBL learning model is effective in improving students' critical thinking ability in the Introduction to Geography material at SMAN 12 Kendari. This PBL model can be used as an alternative learning strategy that encourages students to be more active and analytical, while also helping teachers create a more student-centered learning process.